The Mediterranean diet and its impact on growth, hormonal balance, and metabolic health: A narrative review - Soliman, Ashraf T; De Sanctis, Vincenzo; Alyafei, Fawzia; AlHumaidi, Noora; Alaaraj, Nada; Hamed, Noor; Ahmed , Shayma; ElSiddig, Sohair; Itani, Maya; Soliman, Nada (Acta Biomedica Atenei Parmensis, 2025)
Background: The Mediterranean diet (MD), rich in fruits, vegetables, whole grains, legumes, nuts, and olive oil, with moderate fish and dairy and limited red meat, is recognized for its cardiometabolic benefits. However, its role in pediatric  and adolescent growth, metabolic regulation, and hormonal balance is still being explored.Objectives: This narrative review evaluates MD’s impact on anthropometric development, metabolic health, gut hormone secretion, and microbiota composition in children and adolescents.Methods: A systematic review of literature from 2000 to 2024 was conducted using PubMed, Scopus, Web of Science and Embase. Studies included randomized trials, observational studies, and meta-analyses assessing MD adherence in pediatric and adolescent populations, with outcomes related to growth, metabolism, hormones, and microbiota. A total of 52 studies involving over 15,000 subjects met the inclusion criteria. Meta-analytical methods and regression analyses were employed.Results: MD adherence was significantly associated with lower prevalence of obesity, improved height standard deviation score (SD), and reduced adiposity. Metabolic improvements included lower LDL, higher HDL, enhanced insulin sensitivity, and reduced type 2 diabetes risk. Hormonal benefits were also noted, with increased glucagon-like peptide 1 (GLP-1) and peptide YY (PYY), and decreased ghrelin levels. Moreover, MD promoted gut microbiota diversity, increasing fatty-acid-producing bacteria (SCFA) producers and reducing inflammatory species. Inflammatory markers, including interleukin-6, C-Reactive Protein, tumor necrosis factor-alpha, were consistently reduced.Conclusion: The Mediterranean diet supports optimal growth, improved metabolic profiles, and favorable hormonal and gut microbiota regulation in children and adolescents. Promotion of the MD in early life may offer a strategic public health approach to mitigate pediatric obesity and metabolic disorders. Further longitudinal and mechanistic studies are warranted.